Telogen effluvium in covid-19 patients: a cross-sectional survey - Ahmad, Faisal; Sajid, Fatima; Bin Haq, Afnan; Rizwan, Shayan; Siraj, Ayesha; Rizwan, Muneeza (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the frequency of telogen effluvium in post-coronavirus disease-2019 patients. Method: The cross-sectional study was conducted at the Department of Dermatology, Pakistan Air Force Hospital, Islamabad, Pakistan, from February 10 to August 10, 2022, and comprised coronavirus disease-2019 patients of either gender aged 14-60 years. Telogen effluvium was defined as diffuse, non-scarring shedding of hair. Patients’ own approximate assessment of the degree of hair loss using 60-second timed hair count for 3 consecutive days was taken as a subjective tool to grade the severity of hair loss per day as mild (<20 hair/day), moderate (20-70 hair/day), severe (71-100 hair/day) and very severe (>100 hair/day). The severity of coronavirus disease-2019 was assessed through high-resolution computed tomography chest severity scoring as mild (0-9), moderate (10-19) and severe (>20). Data was analysed using SPSS 23. Results: Of the 160 patients, 83(51.9%) were males. The overall mean age was 30.72±6.026 years, and the mean coronavirus disease-2019 severity score was 12.83±5.16. Telogen effluvium was noted among 46(28.8%) patients; 8(17.4%) mild, 21(45.7%) moderate, 12(26.1%) severe, and 5(10.8%) very severe. Females had a significantly higher frequency of telogen effluvium compared to males (p<0.01). Conclusion: Telogen effluvium was noted as one of the frequent consequences of the coronavirus disease-2019, and it was strongly associated with the female gender. Key Words: COVID-19, Pandemic, Real-time polymerase chain reaction, Severe acute respiratory syndrome coronavirus-2.